Parameters Affecting Coating Uniformity of Alkali -Activated Material Coated Fertilizer - Hakim H, Luqman; Zilati KZ., Ku.; Harris N., Muhammad (International Journal of Engineering and Technology, 2018)
The establishment of Controlled Release Urea (CRU) in agriculture industry has given a great significant outcome towards the development of economy while preserving the environment. As it is developed through a coating process, it does not only help to increase fertilizerâ€™s efficiency, but also minimize the loss of nutrients into the soil and environmental pollution. There are many types of coating materials that have been extensively studied as well as applied in everyday life from pharmaceutical industry to engineering industry such as in pharmaceutical tablet, road construction and corrosion control of steel structures like offshore platforms. In this research, the alkali-activated material composite has been developed as a new coating material and is introduced as the main coating material for the CRU. In term of environmental friendliness, alkali-activated material (AAM) isÂ considered better than sulphur and polymer. However, the combination of fly ash and sodium hydroxide (NaOH) solution producing the AAM paste needs further research since it can be categorized as a novel coating material for CRU. It is also to ensure the suitability of it to be used as a coating material on urea fertilizer. A significant coating thickness along with good hardness strength can produce promising coated urea granules characteristics. Two parameters have been studied for this research to identify its effect towards coating thickness and hardness strength of coated urea granules which are inlet air pressure and spraying rate. These two parameters are identified to be crucial in enhancing the characteristics of coated urea granules. Â Â